Early Chilhood, Characteristic and Creative-Social Development - Subur Subur (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
Every child born, not only has talent and creative potential, but also has social tendency. Talent and creative and social potential are important capital to determine child future. Talent and creativity can develop optimally when they are coached intensely and professionally. Well-developed talent will be very helpful for children future. Every parent wants to have creative and sociable child but, not all parents understand how to develop their children’s creative and social potential. Therefore special strategy to develop creative and social potential for early childhood, i.e.: playing, storytelling, singing, creating product, imagination, exploration, experiment, grouping, imitating, cooperative playing and sharing. The characteristics of social development are often associated by the skill of cooperation, rotation, initiative/leadership, sharing, discipline and participation.